Photocatalytic Hydrogen Production from Formic Acid Solution with Titanium Dioxide with the Aid of Simultaneous Rh Deposition - Mahmudul Hassan Suhag; Ikki Tateishi; Mai Furukawa; Hideyuki Katsumata; Aklima Khatun; Satoshi Kaneco (ChemEngineering, 2022)
Photocatalytic hydrogen production was studied with a formic acid solution with titanium dioxide (TiO2) with the aid of simultaneous Rh deposition. The optimum conditions were as follows: Rh loading, 0.1 wt%; formic acid concentration, 1.0%; solution, pH 2.2; temperature, 50 °C. Under the optimum conditions, the photocatalytic hydrogen production with TiO2 by the simultaneous deposition of Rh was 5.0 mmol g−1, 12.2 mmol g−1 and 16.0 mmol g−1 after 1 h, 3 h and 5 h of irradiation time for black light, respectively. Rh/TiO2 photocatalysts were characterized by XRD, SEM, photoluminescence spectra, diffuse reflectance spectra and the BET surface area. The reaction mechanism of photocatalytic hydrogen production from formic acid by Rh/TiO2 was also proposed.